Pedagogical Process in Science at Government Secondary Schools of Odisha - Krishnan, Dhanya (Voices of Teachers and Teacher Educators, 2019)
Considering the broader aim of Science education as cultivating scientific literacy among citizens of the country by developing a sense of inquiry, rational thinking, and objectivity through varied exploratory activities, examining the process of science learning in schools is very significant. The intention of this paper is to present the findings related to pedagogical processes in Science with respect to content, pedagogical strategy employed, resource management and assessment. In this exploratory research, qualitative survey method has been adopted and 51 schools from 6 districts of Odisha participated. The pedagogical process is captured using classroom observation, FGD with students and interview with Science teachers. A checklist was used to examine the laboratory facilities in the schools. It was found that activity based classes were very limited. A teacher centred process with question and answer session was observed predominantly in the classrooms. Hands on activity as a pedagogic medium was not much explored in the classrooms. However, in a few schools, efforts are made to motivate students by involving them in science exhibition and science quizzes. It was also found that laboratory and ICT tools were not integrated to the teaching-learning processes. More involvement of teachers and their commitment to the profession may lead to better planning of the lesson. The findings indicate that there should be conscious effort from all the stakeholders to revamp science learning processes in Government Secondary schools of Odisha.